Heritability of brain activity related to response inhibition: a longitudinal genetic study in adolescent twins - Anokhin, Andrey P. (Int J Psychophysiol, 2017)
The ability to inhibit prepotent but context- or goal-inappropriate responses is essential for adaptive self-regulation of behavior. Deficits in response inhibition, a key component of impulsivity, have been implicated as a core dysfunction in a range of neuropsychiatric disorders such as ADHD and addictions. Identification of genetically transmitted variation in the neural underpinnings of response inhibition can help to elucidate etiological pathways to these disorders and establish the links between genes, brain, and behavior. However, little is known about genetic influences on the neural mechanisms of response inhibition during adolescence, a developmental period characterized by weak self-regulation of behavior. Here we investigated heritability of ERPs elicited in a Go/No-Go task in a large sample of adolescent twins assessed longitudinally at ages 12, 14, and 16. Genetic analyses showed significant heritability of inhibition-related frontal N2 and P3 components at all three ages, with 50 to 60% of inter-individual variability being attributable to genetic factors. These genetic influences included both common genetic factors active at different ages and novel genetic influences emerging during development. Finally, individual differences in the rate of developmental changes from age 12 to age 16 were significantly influenced by genetic factors. In conclusion, the present study provides the first evidence for genetic influences on neural correlates of response inhibition during adolescence and suggests that ERPs elicited in the Go/No-Go task can serve as intermediate neurophysiological phenotypes (endophenotypes) for the study of disinhibition and impulse control disorders.